Long-Term Clarity of High-Water-Content Hydrophobic Acrylic Intraocular Lens: A 3-Year Randomized Comparison with a Hydrophobic Lens of Similar Material and Design - Akira Miyata; Kazunori Miyata; Keiichiro Minami (Ophthalmology and Therapy)
Abstract Introduction This randomized prospective study aimed to quantitatively evaluate 3-year visual function, glistenings, and surface light scattering following the implantation of high-water-content hydrophobic acrylic intraocular lenses (IOLs). Methods One-piece high-water-content IOLs (Clareon® SY60WF; group C) and control hydrophobic acrylic IOLs (Vivinex XY1; group V) were randomly implanted in 120 Japanese participants (120 eyes). Subsequently, the corrected distance visual acuity (CDVA), contrast sensitivity, glistening-derived microvacuoles (MVs), and surface light scattering were examined up to 3 years postoperatively. EPCO software was used to confirm the absence of postoperative capsule opacification to ensure that it did not influence the outcomes. MVs within a 15 × 4 mm area were counted using a slit-lamp microscope. Surface light scattering was evaluated using densitometry. Finally, outcomes were compared among the groups. Results Overall, 116 eyes were compared (58 eyes each in groups C and V). No differences in the CDVA, contrast sensitivity, and MVs were observed between the groups. The mean densitometry value in group C was significantly higher (P = 0.027) than in group V, increasing significantly from the values recorded at 1–4 weeks, although the change was clinically small (0.29%). Conclusion This randomized comparative study confirmed non-inferiority in visual function of eyes with Clareon IOLs. A 3-year comparison indicated no difference in glistening suppression, CDVA, or contrast sensitivity, whereas a slight increase was observed in surface light scattering. Trial Registration Registered in the Japan Registry for Clinical Trials (identifier jRCTs032190093).